The transparency of the atmosphere over India - IYER, NV (MAUSAM, 1986)
The transparency of the atmosphere (q) over India has been studied from global (G) and diffuse solar radiation (V) measurements in India, The ratio DIG and D/G-D which indicate the scattering have also been studied for all the stations.